The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1080/10601320701351193
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Optical Limiting Properties of Polyurethane Containing Long Conjugated Chromophores

Abstract: Two functional polyurethanes (P1 and P2) bearing a large p electron conjugated chromophoric pendant were synthesized and characterized by FT-IR, 1 H-NMR and UV-Vis absorption spectra. Their optical limiting properties were evaluated. The results show that P1 and P2 show novel optical limiting properties, which are assigned to a long p electron conjugated chromophoric pendant. It was found that their optical limiting properties were affected simultaneously by solution concentration and P2 displays a better opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…It can be found that higher concentration (lower transmittance) solution exhibits better performances. Similar results were also found by Kojima's and our previous publications . Solution with higher concentration has more molecules per unit volume, thereby absorbing the energy of the harsh laser more efficiently.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It can be found that higher concentration (lower transmittance) solution exhibits better performances. Similar results were also found by Kojima's and our previous publications . Solution with higher concentration has more molecules per unit volume, thereby absorbing the energy of the harsh laser more efficiently.…”
Section: Resultssupporting
confidence: 91%
“…Similar results were also found by Kojima's 48 and our previous publications. 49 Solution with higher concentration has more molecules per unit volume, thereby absorbing the energy of the harsh laser more efficiently.…”
Section: Resultsmentioning
confidence: 99%
“…Water-soluble organic polymeric dyes were also found to possess third-order nonlinearity. Thin films of polymers 433 and 434 (Chart ) showed nonlinear absorption in the IR with a TPA coefficient of 55 and 18 cm/GW, respectively. , Functional polyurethanes 435a , b were synthesized, and their OL properties were evaluated. , These were ascribed to the presence of long π-electron conjugated chromophoric pendants. Polymer 435b displayed better OL properties than 435a at the same value of linear transmittance, although 435a had a larger χ (3) (4.28 × 10 –11 esu) than 435b (0.87 × 10 –11 esu) from RSA mechanism.…”
Section: Organic Materialsmentioning
confidence: 99%
“…959,960 Functional polyurethanes 435a,b were synthesized, and their OL properties were evaluated. 961,962 These were ascribed to the presence of long π-electron conjugated chromophoric pendants. Polymer 435b displayed better OL properties than 435a at the same value of linear transmittance, although 435a had a larger χ (3) (4.28 × 10 −11 esu) than 435b (0.87 × 10 −11 esu) from RSA mechanism.…”
Section: Polymeric Materialsmentioning
confidence: 99%
“…(2) and 4-((4-(bis(2-hydroxyethyl)amino)phenyl)diazenyl) benzaldehyde (3) were synthesised by the methods of Su et al [21] and Ledoux et al [22] respectively. Tetraethyl ((9,9-bis(2-ethylhexyl)-fluorene-2,7-diyl)bis(methylene))bis(phosphonate) was synthesised by an adaptation of the method of Mongin et al [23], while tetraisopropyl ((2-((2-ethylhexyl)oxy)-5-methoxy-1,4-…”
Section: Preparation Of Chromophoresmentioning
confidence: 99%